The Urgency of Legal Protection for COVID-19 Vaccine Quality Assurance During the Pandemic in Indonesia - Maria Madalina; Moch Syafrudin Dwisapto Laxamanahady (HUKUM PEMBANGUNAN EKONOMI, 2022)
The implementation of vaccination has started in the first stage and will continue until the fourth stage, but in reality there are still many pros and cons that occur in the community. For people who are pro against the implementation of the COVID-19 vaccination, there are some people who accept that this vaccination is carried out as soon as possible in Indonesia because it is considered a solution in order to resolve the COVID-19 pandemic in Indonesia. As for the people who are against it, where some of these people refuse to carry out vaccinations because they think the vaccine is not necessarily safe for their bodies, and are worried about the side effects that arise after the implementation of the COVID-19 vaccination. Then there are also many questions that arise among the public regarding legal protection for them after getting the COVID-19 vaccine. So from research on legal protection if side effects occur after the implementation of COVID-19 vaccination for people in Indonesia, it is quite important, considering that the legal basis that guides the implementation of this vaccination is still new and is still being debated among the public. Where there are many regulations governing the implementation of this COVID-19 vaccination, even in every region in Indonesia, each region has the authority of regional government regulations.